2013
DOI: 10.1016/j.neuroscience.2013.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Drugs that prevent mouse sleep also block light-induced locomotor suppression, circadian rhythm phase shifts and the drop in core temperature

Abstract: Exposure of mice to a brief light stimulus during their nocturnal active phase induces several simultaneous behavioral or physiological responses, including circadian rhythm phase shifts, a drop in core body temperature (Tc), suppression of locomotor activity and sleep. Each response is triggered by light, endures for a relatively fixed interval and does not require additional light for expression. The present studies address the ability of the psychostimulant drugs, methamphetamine (MA), modafinil (MOD) or ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 63 publications
0
21
2
Order By: Relevance
“…It has been shown previously that application of an adenosine agonist attenuates the light‐induced phase delays in behaviour, which are restored by an adenosine receptor antagonist (Elliott et al ., ; Sigworth & Rea, ). In contrast, a recent study showed that caffeine administration blocks light‐induced phase delays; however, the dose applied was three times larger, and the activity of the animals was very much reduced under these conditions (Vivanco et al ., ). We found that at the level of the SCN, caffeine restored light responses.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown previously that application of an adenosine agonist attenuates the light‐induced phase delays in behaviour, which are restored by an adenosine receptor antagonist (Elliott et al ., ; Sigworth & Rea, ). In contrast, a recent study showed that caffeine administration blocks light‐induced phase delays; however, the dose applied was three times larger, and the activity of the animals was very much reduced under these conditions (Vivanco et al ., ). We found that at the level of the SCN, caffeine restored light responses.…”
Section: Discussionmentioning
confidence: 97%
“…Deep body temperature increased in the day and decreased in the night, while peripheral cutaneous temperature was elevated in the night. These diurnal changes in body temperature are reportedly necessary for balanced heat production and heat dissipation in the body and are deeply involved in the emergence of REM/non-REM sleep [25,26]. As a possible link between this phenomenon and the mechanism of sleeping, peroxisome proliferator-activated receptor alpha (PPARα) agonists and other drugs that accelerate lipid metabolism have been reported to be involved in the regulation of the biological clock and improvement of the circadian rhythm in sleep disorders [27].…”
Section: Discussionmentioning
confidence: 99%
“…The biphasic effects of a higher dose of harmaline (15 mg/kg) on home-cage or locomotor activity revealed in mice (Figures 1 and 4) using the automated Telemetry system [3840] is consistent with the very recent findings on biphasic effects of harmaline on mobility (locomotor activity) obtained from rats using fully automated Force Plate Actimeters [41]. However, different from a partial attenuation of the late-phase hyperactivity by Lu AF21934, a positive allosteric modulator of metabotropic glutamate receptor 4 (mGlu4) [41], the present study showed a complete attenuation of the early-phase hypoactivity by 5-HT 1A receptor antagonist WAY-100635 (Figure 4).…”
Section: Discussionmentioning
confidence: 99%